Mangroves in Disaster Risk Reduction: Global Trends and Knowledge Gaps - Lola Adres Yanti; Kamarullah Kamarullah; Astri Winda Siregar (Journal of Innovative and Creativity, 2026)
Background. Mangrove ecosystems have increasingly been recognized as important components of disaster risk reduction (DRR), particularly in mitigating the impacts of coastal hazards such as tsunamis, storm surges, and coastal flooding. Alongside the growing influence of climate change adaptation and nature-based solutions, scholarly interest in mangroves has expanded across multiple disciplines. However, the overall development, thematic orientation, and existing gaps within mangrove-based DRR research remain insufficiently synthesized. The study’s objective was to examine the evolution, disciplinary structure, dominant themes, and underrepresented areas of global research on mangroves in the context of DRR. Materials and methods. This study employed a bibliometric approach to analyze peer-reviewed journal articles and review papers indexed in the Scopus database between 2000 and 2026. Descriptive analysis, keyword co-occurrence networks, thematic mapping, thematic evolution analysis, and geographic collaboration analysis were conducted using Biblioshiny and supporting analytical tools to identify publication trends, subject area distributions, core journals, thematic structures, and spatial research patterns. Results. The findings reveal a substantial increase in mangrove-based DRR research over time, particularly following major coastal disasters and during the recent climate-resilience era. The literature is dominated by environmental and earth sciences and primarily framed around ecological protection, ecosystem services, and hazard mitigation. In contrast, governance, preparedness, social vulnerability, and policy-oriented dimensions remain weakly represented. Thematic evolution indicates a shift toward climate-related and ecosystem-based approaches, alongside persistent conceptual gaps. Conclusions. This study concludes that while mangroves are well-established as ecological assets in DRR studies, their role as socio-ecological infrastructures remains underexplored. Advancing mangrove-based DRR requires greater integration of governance, preparedness, and social perspectives to enhance policy relevance and support sustainable coastal resilience.